Factors Associated with Pain during Vascular Access Intervention Therapy. Issue 10 (November 2015) - Muromiya, Yasuto; Nagai, Kojiro; Yokota, Narushi; Okada, Daigo; Suenaga, Takehiro; Ueda, Yuka; Kawahara, Kana; Kanayama, Hiroomi; Minakuchi, Jun; Tsuchida, Kenji
Objective: The objective of this study is to investigate and compare factors associated with pain during vascular access intervention therapy. Subjects and methods: Fifty patients provided informed consent to participate in a survey of pain by questionnaire after receiving dialysis treatment at our hospital. Balloons for use during the procedure were chosen at random in this prospective randomized control study. A numeric rating scale (NRS) was used for pain assessment. Results: A semi-compliant balloon caused significantly worse pain as compared with the other types of balloons (NRS, 7.67 ± 1.57 vs. 6.02 ± 1.89; p<0.05). There was no correlation between maximum inflation pressure and pain, or between age and pain, and no difference between diabetic and non-diabetic patients. A comparison among vascular dilation locations, as well as a comparison of AVF with AVG also revealed no significant differences. Conclusions: The reason for severe pain with use of the semi-compliant balloon as compared with the other types might have been due to its characteristics during inflation, as increased diameter leads to an increase in pressure. Mismatching of balloon diameter to vascular diameter may also increase pain.